Social media attention to research on olive oil: public opinion and research - Montesi, Michela; Fernández Bajón, María Teresa (Revista General de Información y Documentación, 2020)
Measurement of societal impact of research in agriculture can be carried out through impact pathways, evaluative tools that allow to reflect innovation as a systemic process, influenced by social factors and driven by the contribution of different actors. However, the multiplicity and diversity of potentially influential actors in innovation processes pose a problem of participation, as it is difficult to involve them in the evaluation processes of agricultural research. This study proposes alternative metrics or altmetrics to measure of the attention that scientific literature receives on social media and as a way to introduce public opinion into evaluation processes. Results suggest that public opinion perceives olive oil research as more significant when it is interdisciplinary.
Keywords: Societal impact of research; alternative metrics; impact pathways; olive oil; interdisciplinarity